EFFECT OF CURRENT RATIO,QUICK RATIO, TOTAL ASSET TURNOVER AND WORKING CAPITAL TURNOVER ON PRICE SHARE IN THE COMPANY OIL SUB SECTOR AND NATURAL GAS LISTED ON Indonesia STOCK EXCHANGE - Rahmat Hidayat; Viery Annisa Gusman (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine and analyze the effect of the Current Ratio on stock prices, to determine and analyze the effect of the Quick Ratio on stock prices, to determine and analyze the effect of total asset turnover on stock prices, to determine and analyze the effect of working capital turnover on stock prices, to determine and analyze the effect of working capital turnover on stock prices. knowing and analyzing simultaneously the effect of Current Ratio, Quick Ratio, Total Asset Turnover and Working Capital Turnover on Stock Prices in Oil and Gas Sub-Sector Companies Listed on the Indonesia Stock Exchange. The sample used in this study were 7 companies from 12 populations in oil and gas sub-sector companies. The data analysis technique in this research uses the Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test), Multiple Linear Regression, Hypothesis Testing (T Test and F Test) and Determination Test. Processing data in this study usingSoftware SPSS (Statistic Package for the Social Sciences) version 24. Based on the results of the study indicate that the Current Ratio has no positive and insignificant effect on stock prices, Quick Ratio has a negative and insignificant effect on stock prices, Total Asset Turnover has a negative and significant effect on stock prices. , Working Capital Turnover has no positive and insignificant effect on stock prices. Meanwhile, Simultaneously Current Ratio, Quick Ratio, Total Asset Turnover and Working Capital Turnover have a significant positive effect on Stock Prices in Oil and Gas Sub-Sector Companies listed on the Indonesia Stock Exchange.Keywords : Current Ratio, Quick Ratio, Total Asset Turnover, Working Capital Turnover and Stock Price